2021
DOI: 10.1177/10439862211034343
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Lethal Violence in Brazil 2000–2017: A Space-Temporal Analysis of Homicides

Abstract: This study investigates the space-temporal growth of homicide rates in Brazil from 2000 to 2017 and identifies determinants of the country’s growth of homicide rates. Data from the Brazilian Information System on Mortality and Censuses are used to estimate growth models combined with spatial statistics and Geographical Information Systems (GIS). Findings show evidence of change in the geographical distribution of lethal violence over time, characterized by a steady increase in the North and Northeast regions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…In addition, Boateng and Dzordzormenyoh (2022) observed that the majority of Brazilians fear violent crime and based on that, have high perceptions of insecurity. Also, it has been argued that citizens’ patterns of insecurity and victimization in Brazil are influenced by factors such as the country's experience with forced occupation and slavery (Aransiola et al, 2022; Dammert, 2012; Valente & Vacchiano, 2021). Likewise, a study by Dammert (2012) identified a positive association between high crime rates and citizens’ perception of insecurity, suggesting that high crime enhances people's sense of insecurity in their neighborhood.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Boateng and Dzordzormenyoh (2022) observed that the majority of Brazilians fear violent crime and based on that, have high perceptions of insecurity. Also, it has been argued that citizens’ patterns of insecurity and victimization in Brazil are influenced by factors such as the country's experience with forced occupation and slavery (Aransiola et al, 2022; Dammert, 2012; Valente & Vacchiano, 2021). Likewise, a study by Dammert (2012) identified a positive association between high crime rates and citizens’ perception of insecurity, suggesting that high crime enhances people's sense of insecurity in their neighborhood.…”
Section: Introductionmentioning
confidence: 99%